Self-Reported Reasons for Participating in Pro-environmental Citizen Science Activities: A Case Study of Butterfly Monitoring in Israel - Tsybulsky, Dina (Frontiers in Education, 2020)
The current study examines the common characteristics of citizen science volunteers and the reasons that lead them to participate in pro-environmental conservation-related activities, specifically in monitoring butterflies. The research was conducted as a case study and involved the use of qualitative and quantitative methods for gathering and analyzing the data. Findings indicate a complex system of self-reported reasons, mostly internal, reflecting participants’ desire to contribute to society, meet with other people, and increase their range of knowledge on the topic. Furthermore, findings indicated that there are shared characteristics among the profiles of citizen science volunteers, which included growing up in a rural setting and encountering significant figures and/or events that led to their love of nature, their strong and deep sense of commitment and concern for nature, and their desire to take active steps to preserve it.